Bobby glow-worm: all aboard - Nash, Margaret; Park, Julie (Ginn Aylesbury, 1994)
"Bobby Glow-Worm" by Margaret Nash and Julie Park tells the charming story of a little glow-worm named Bobby who feels different from the other insects. While they sparkle and shine, Bobby struggles to glow brightly. As he embarks on a journey to discover his unique talents, he learns the importance of self-acceptance and the value of being true to oneself. The story is beautifully illustrated and conveys themes of individuality, friendship, and finding one's own light, making it an uplifting read for young children.